Primary histiocytic sarcoma arising in the head and neck with predominant spindle cell component - Zhao XF; Ord Robert A; McClure Shawn A; Sailey Charles J; Alexiev Borislav A; Papadimitriou John C (BMC, 2007)
Abstract This is the first case report of Histiocytic Sarcoma (HS) with predominant spindle cell component occurring in the head and neck region of a 41-year-old man. The tumor was composed of sheets of large round to oval cells with pleomorphic vesicular nuclei, prominent nucleoli and abundant eosinophilic cytoplasm. Multinucleated forms, numerous mitoses, and tumor necrosis were also noted. Sheets, fascicles, and whorls of spindle cells with spindled to ovoid vesicular nuclei, small to medium-sized distinct nucleoli, and eosinophilic cytoplasm were frequently observed. Immunohistochemical staining in the tumor cells was positive for CD163, CD68, lysozyme, CD45, and NSE. Focal expression of CD4 and S-100 was also noted. Electron microscopy demonstrated an abundance of lysosomes in the cytoplasm of tumor cells. Chromosome study revealed a 57-80 hyperdiploid [7]/46, XY [13] karyotype, including 3 to 4 copies of various chromosomes. The immunohistochemical and ultrastructural findings confirmed the diagnosis of HS.